THE EFFECT OF PRINCIPAL LEADERSHIP ON WORK CLIMATE AND TEACHER PERFORMANCE - Melyana R Pugu; Siminto; Muthmainnah Mursidin (INJOSEDU: International Journal of Social and Education, 2025)
This study aims to investigate the effect of principal leadership on work climate and teacher performance using the literature review method. The results show that principal leadership plays a vital role in creating a conducive work climate, which significantly affects teacher performance. Inclusive and participatory leadership styles, such as transformational leadership, are associated with increased teacher motivation and commitment, which in turn improves the quality of teaching and learning. Research also shows that effective principals are able to identify and overcome challenges in the working climate, improve collaboration among teachers and implement policies that support teachers' professional development. Thus, principal leadership has an impact not only on improving teacher performance but also on creating a positive and supportive work environment.